The Effectiveness of INTAKO's Small and Medium Industry Revitalization Program in Sidoarjo Regency - Eka Yulianti; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to analyze and describe the effectiveness of the INTAKO Small and Medium Industry revitalization program in Kedensari Village, Tanggulangin District. The research method used is descriptive with a qualitative approach. Informants are determined by purposive sampling, including the Head of Industry and Industrial Extension Staff, INTAKO Supervisors and Staff, as well as Small and Medium Industry Actors and INTAKO Visitors. Data analysis comes from Miles and Huberman data, namely through data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate the effectiveness of the INTAKO Small and Medium Industry revitalization program in Kedensari Village, Tanggulangin District seen from three indicators, namely the achievement of goals seen from the period of completion of the program in line with the legal basis, namely the Regulation of the Minister of Industry of the Republic of Indonesia Number 09/M-IND/PER/2/ 2016 concerning Technical Guidelines for the Use of Special Allocation Funds for the Development of Industrial Facilities for the 2016 Fiscal Year, however, it is necessary to realize the program in accordance with the action plans that have been made previously. The target of the revitalization program is Tanggulangin integrated tourism or 3 in 1 tourism. Integration is seen from the communication ability of the program seen with the Industry and Trade Office of Sidoarjo Regency socializing the program in 2017 and the ability to understand the program is seen from the people who understand the program by maintaining the existing infrastructure facilities. revitalized. Adaptation is done by increasing human resources through workshops and online sales training and the need for online marketing training. Then the adaptation of infrastructure is seen from the improvement of infrastructure facilities in the revitalization program but the need to improve infrastructure specifically in the INTAKO Cooperative showroom in Kedensari Village.